On Philosophical Basis of the Theory of Values - Lozuraitis, Albinas (Problemos, 1976)
The article discusses the main trends of philosophy which have served as a basis for the relatively independent philosophical discipline called axiology. The main attention is paid to two problems of cardinal importance – the nature and essence of the theoretical mastering of reality and the definition of the status of philosophy in the cognition of the world resulting therefrom. The positive solution of these problems by the Marxist philosophy allows to define to a considerable degree its attitude to axiology. The article emphasizes the idea that the Marxist methodology had served as a basis of the scientific approach to the problem of values long before it acquired the form of antinomy in axiology.